Transparency and transplants: it is possible? Bioethical dilemmas in assigning organs - Zúñiga-Fajuri, Alejandra (Acta Bioethica, 2017)
Paucity of information on how waiting lists are managed and limited resources allocated is all too common across most fields of medicine. Organ transplantation is front and center among areas where non-transparency and the attendant perception of injustice causes the most damage, with studies showing a close link between the refusal to donate organs and mistrust in the system. Confidence in organ allocation mechanisms needs to be restored to alleviate the shortage crisis. Insofar as the nature of the ensuing final decisions is moral rather than medical, public involvement in addressing the bioethical issues arising from the allocation of limited resources becomes imperative.